The potential of student as partners approaches for humanitarian developments - Lowe, Tom; Moxey, Maria (International Journal for Students as Partners, 2024)
This article explores the potential for students-as-partners models developed in the scholarship of teaching and learning and educational development fields to be expanded to new agendas such as humanitarian developments and other agendas related to the so-called civic university. There is a growing appetite for students and staff to work in partnership due to the mutual benefits for both parties (Mapstone et al., 2017), yet the majority of the published works on students as partners is almost exclusively reporting upon partnership activities relating to curriculum and wider student experience developments in higher education. This paper explores the literature on best practice for working with students as partners in order to create new recommendations for how the students-as-partners model can be applied successfully for community and humanitarian development projects, rather than curricular, teaching, or research projects By drawing on literature from student voice, student engagement in quality assurance, and co-design, this paper will highlight the great potential of student-staff partnerships for addressing other development agendas globally.